EVALUATION OF MILTEFOSINE AGAINST LEISHMANIA MAJOR (MRHO/IR/75/ER): IN VITRO AND IN VIVO STUDIES - J. Esmaeili; M. Mohebali; G. H. Edrissian; S. M. Rezayat; M. Ghazi-Khansari; S. Charehdar (Acta Medica Iranica, 2008)
Cutaneous leishmaniasis is endemic in 88 different countries. There are an estimated 1.5 million new cases each year, with over 90% occurring in Afghanistan, Algeria, Iran, Iraq, Saudi Arabia, Syria (Old World) and in Brazil and Peru (New World). Miltefosine is effective in vitro and in vivo against Leishmania species and it was demonstrated efficacy in animals via the oral route. This study is the first one for evaluating the effect of miltefosine on cutaneous leishmaniasis of L. major (MRHO/IR/75/ER) by in vivo and in vitro studies in the BALB/c mouse model. As it was shown, miltefosine has a better effect on reduction of size of lesion compared to Glucantime®, also it was not significant by statistical analysis. The results of this study show that miltefosine has a good activity against the proliferation of amastigotes of L. major. The results suggest that oral miltefosine might be a promising approach for developing new anti-Leishmanial drugs.